Prevalence and Risk Factors of Surgical Treatment for Klippel–Feil Syndrome - Ding, Linyao; Wang, Xin; Sun, Yu; Zhang, Fengshan; Pan, Shengfa; Chen, Xin; Diao, Yinze; Zhao, Yanbin; Xia, Tian; Li, Weishi; Zhou, Feifei (Frontiers in Surgery, 2022)
Background: Recently, there are some reports on surgical treatment for Klippel-Feil syndrome, but the prevalence and risk factors of surgery have not been well evaluated. This study aimed to find the prevalence and the potential risk factors of surgical treatment. Methods: A retrospective radiographic review of 718 Klippel-Feil syndrome patients at Peking University Third Hospital from January 2010 to October 2017. Parameters included age, gender, deformity, cervical instability, as well as Samartzis classification and surgical treatment. Based on the surgical treatment, patients were divided into surgery group and non-surgery group. Prevalence and possible risk factors of surgical treatment were assessed. Results: A total of 718 Klippel-Feil syndrome patients were consisted of 327 males and 391 females, with an average age of 46.8 years old. Based on Samartzis classification, 621 patients (86.5%) were classified as Type I, 48 patients (6.7%) were Type II, and 49 patients (6.8%) comprised a Type III. The most common fused segments were C2-C3 (54.9%) and C5-C6 (9.3%). Of all the 718 patients, 133 (18.5%) patients underwent surgical treatment, mainly through the posterior approach (69.9%). The clinical factors included age, gender, deformity, instability and Samartzis classification. It seemed that male patients had more possibility to take the surgical treatment (P<0.001). Patients with instability (P<0.001) or patients with deformity (P=0.004) were more likely to have surgery. All the three variables were included into the binary regression analysis. Finally, gender (P<0.001) and unstable joint (P<0.001) were identified to be independently associated with the surgical treatment. Gender was the most crucial risk factor with males 2.39 times more likely to have surgical treatment, and patients with instability were 2.31 times more likely to perform surgery. Conclusion: The prevalence of KFS patients that performed the surgical treatment was 18.5%, and most of them via the posterior approach. As for the risk factors, gender and instability were finally confirmed to be independently associated with surgical treatment.